Meta-Analysis of Associations between Maternal Age, Low Hemoglobin Level during Pregnancy, Low Birth Weight, and Preterm Birth - Kusumawati, Ima; Murti, Bhisma; Pamungkasari, Eti Poncorini (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Maternal age <19 years and anemia in pregnancy are often associated with adverse neonatal outcomes. This study aims to analyze the relationship between maternal age <19 years and anemia in pregnancy (Hb <11 g/dL) on the incidence of low birth weight babies (LBW) and premature birth. Subjects and Method: The research meta-analysis took cohort studies published in 2018-2022. The PICO formulation used: the population is pregnant women, the intervention consists of groups of pregnant women aged <19 years and pregnant women with anemia (Hb<11 gr/dL), comparison is the group of pregnant women aged 20-35 years and pregnant women are not anemic while Outcomes were LBW and premature birth. Search articles through databases: PubMed, springer, science direct and google scholar with the keywords “Adolescence pregnancy OR young OR Teenage AND Pregnancy AND neonatal outcome OR Low birth weight OR preterm birth OR Low weight”, “Anemia OR Maternal anemia AND Neonatal outcome OR Preterm birth